DEVELOPMENT OF E-MODULES FOR LEARNING TRADITIONAL GANDANG TORAJA MUSIC - Latuni, Glenie; Jesika, Jesika (Universitas Labuhanbatu, 2025)
Purpose – This research aims to: (1) Identify the content of the electronic learning module on traditional Gandang Toraja music developed for 10th grade high school students; (2) Develop an electronic learning module on traditional Gandang Toraja music as learning material for 10th grade high school students; (3) Test the feasibilityfeasibility of the electronic learning module on traditional Gandang Toraja music for 10th grade high school students;.Methodology – This study is an R&D (Research and Development) study based on the ADDIE model. The subjects of this study are 10th-grade students at SMA Negeri 2 North Toraja, with data collected through observation, interviews, documents, and tests. The data collection instruments used include observation sheets, document sheets, interview sheets, and product evaluation sheets, which include expert material assessment sheets, expert media assessment sheets, student responses, and teacher responses. Data analysis techniques include both quantitative and qualitative methods.Findings – The results of this study are the outcome of developing an electronic learning module product featuring traditional South Sulawesi music material, specifically Gandang Toraja. This electronic module is based on a flipbook using the Flip PDF Corporate Edition 2.4.10 application, which can be accessed via a computer or laptop. The electronic learning module was evaluated by subject matter experts with “very good